2008
DOI: 10.1111/j.1432-2277.2008.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus, an important risk factor for tuberculosis in immunocompromised: experience with kidney transplantation

Abstract: Summary Little is known about the role of hepatitis C virus (HCV) infection in the development of tuberculosis (TB) in patients with immunosuppression. We performed a retrospective case–control study (1:4) to investigate by univariate and multivariate logistic regression analysis the importance of HCV infection in the development of TB in a cohort of kidney transplant recipients (KTR). TB was diagnosed in 16 out of 2012 (0.8%) KTR between 1976 and 2004. The percentage of HCV‐positive patients was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 16 publications
1
33
1
1
Order By: Relevance
“…Risk factors of TB transmission to kidney transplant recipients are direct contact with a TB carrier [17], blood group AB [18], hepatitis C [19], and allograft dysfunction with creatininemia higher than 1.5 mg/dl [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors of TB transmission to kidney transplant recipients are direct contact with a TB carrier [17], blood group AB [18], hepatitis C [19], and allograft dysfunction with creatininemia higher than 1.5 mg/dl [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a significant relationship between development of tuberculosis and presence of HCV infection in renal transplant recipients [64] , but it is not clear why HCV-positive recipients are more susceptible to this infection. Immunosuppression and diabetes are two possible explanations [63] .…”
Section: After Kt: Infectionsmentioning
confidence: 99%
“…La principal dificultad para obtener datos precisos está dada por la calidad de los estudios donde la mayoría son retrospectivos y series de casos. Además, la información disponible se refiere fundamentalmente a trasplante renal y por tanto, no es necesariamente aplicable a los receptores de otros trasplantes [8][9][10] . Dentro de los factores de riesgo descritos para el desarrollo de TBC están la terapia con OKT3 o anticuerpos anti-linfocitarios 6 , diabetes mellitus, enfermedad hepática crónica, co-infecciones (CMV, micosis profunda, neumonía por Pneumocystis jiroveci y Nocardia sp) 11 , edad avanzada y el uso de ciclosporina.…”
Section: Epidemiologíaunclassified